How Destination Value and Tourist Engagement in Destination Image Affect Tourist Loyalty - Djatola, Hariyanto R; Hilal, Nur; Sutomo, Maskuri (ETIKONOMI, 2025)
Research Originality: There is only a limited amount of empirical research that examines how the post-visit destination image is shaped by tourist experiences with perceived high destination value and its impact on tourist loyalty within the context of ecotourism.Research Objectives: The aim is to understand the role of perceived value and tourist engagement in the post-visit destination image concerning tourist loyalty within the context of ecotourism.Research Methods: A cross-sectional research design was used and a sample of 326 travelers was drawn from an unknown pool of customers. The analysis method used in this study utilizes SEM.Empirical Results: Destination value directly influences both tourist engagement and loyalty. Additionally, tourist engagement directly affects tourist loyalty; however, it does not mediate between destination image and tourist loyalty.Implications: The results suggest several practical implications for destination managers, who should focus more on the ecotourism context when designing visitor experiences as a source of sustainable information, as well as for governments and nonprofit organizations aiming to promote ecotourism.JEL Classification: M30, M31, M310How to Cite:Djatola, H. R., Hilal, N., & Sutomo, M. (2025). How Destination Value and Tourist Engagement Image Affect Tourist Loyalty? Etikonomi, 24(1), 97 – 118. https://doi.org/10.15408/etk.v24i1.34698.